THEORETICAL AND LEGAL ISSUES OF TAX RELATIONS REGULATION - Bohodir o’g’li, Ibragimov Boburshoh (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the theoritical and legal issues of tax relations. On this case, regulation of the relations were stated in the development of the taxing conditions of Uzbekistan. It analysed and concluded with both theoritical and methodological points of the republic of Uzbekistan.